MATLAB-Based Visualization of Helical Structures and Their Applications - Rokaya, Bhim Bahadur (Academic Journal of Mathematics Education, 2022)
A helix is a type of smooth space curve, i.e. a curve in three-dimensional space. This study aims to present a MATLAB-based approach to visualize helical structures and to demonstrate their applications in various fields. As a qualitative study, primary and secondary sources of data have been consulted. Primarily, observing the real-life activities of humans and secondly, the analysis of archival documents such as related research articles, analytical books, and related reports. In conclusion, most of the architectural work in the world is possible by different types of geometrical design through the helix. It also found that we can visualize the different types of helices by using MATLAB in mathematics teaching. The implication of helix is everywhere in different fields and areas such as constructing a basket, screw, etc. Finally, we used helical concepts related to daily life activities in the field of instruction in the mathematics classroom.